U źródeł zjawiska odwoływania się do potencji ościennych w polskich sporach wewnętrznych – casus roku 1730 - Kosińska, Urszula (Studia z Dziejów Rosji i Europy Środkowo-Wschodniej, 2019)
Tekst, poświęcony misji Antoniego Potockiego do carycy Anny Iwanowny w imieniu prymasa Teodora Potockiego z VII–VIII 1730 r., ukazuje proces utrwalania praktyki odwoływania się w polskich sporach wewnętrznych do pośrednictwa Rosji, a tym samym stopniowej utraty suwerenności przez Rzeczpospolitą. At the Origins of the Appealing to Neighbouring Powers in Internal Polish Disputes – the Case of the Year 1730 In 1730, on behalf of Primate Teodor Potocki, his nephew Antoni, Pantler of Lithuania, went to Moscow. Under the guise of congratulating his cousin Anna Ivanovna on her accession to the throne, the primate gave her a memorial in which he denounced the alleged plans for the partition, absolutism and succession of King Augustus II, hostile to the Commonwealth. In fact, the mission’s goal was to obtain Russia’s support in the fight against the king for the distribution of the offices of hetman, and especially the office of Grand Hetman of the Crown, which the king intended for Stanisław Poniatowski. Antoni Potocki also presented the empress his own secret “Points”. Under the guise of efforts to fulfil Russian obligations in the case of Livonia and Courland, he held talks in Moscow about the takeover by the Potockis of the estates Hory Horki in Lithuania bought by A. Menshikov some time ago. In public matters, he received empty promises, only in favour of his private demands. He also received help from Russia in the process of destroying the Grodno Sejm of 1730. Under the guise of supporting his “relatives”, the empress achieved her overarching goal, which was to maintain the anarchic status quo in the Commonwealth. The curse of Potocki’s mission shows the mechanisms contributing to the consolidation in public life of the Saxon times of the practice of appealing by the Polish elite to Russia’s mediation in internal disputes, and thus to the gradual loss of sovereignty. The annexes present the texts of both secret memorials forwarded to empress by A. Potocki. У истоков явления обращения к соседним державам в польских внутренних спорах – случай 1730 года В 1730 г. в Москву направился от имени примаса Теодора Потоцкого его племянник Антоний, литовский стольник. Под предлогом поздравить свою кузину Анну Ивановну по случаю вступления на российский престол, примас передал ей письмо, в котором разоблачал, вражеские Речи Посполитой, мнимые планы короля Августа II касательно раздела страны, абсолютистской власти и престолонаследия. В действительности, целью посольства было получение поддержки России в борьбе против короля за распределение гетманских чинов, особенно Великой коронной булавы, которую король предназначил, минуя Пилявитов, для Станислава Понятовского. А. Потоцкий представил императрице также собственные тайные «Пункты». Под предлогом хлопотания за выполнение российских обязательств по Ливонии и Курляндии, Потоцкий вел в Москве переговоры о завладении Потоцкими, купленным когда-то А. Меншиковым имением Горы-Горки в Литве. Ответом на публичные дела были пустые обещания, зато российская сторона положительно отнеслась к его личным требованиям. Потоцкий получил также помощь России в процессе уничтожения Гродненского сейма 1730 г. Под предлогом поддержки «родственников» императрица осуществила свою высшую цель, которой, уже давно, была поддержка в Речи Посполитой анархического статус-кво. История миссии Потоцкого показывает механизмы, способствовавшие укреплению в общественной жизни саксонских времен практики обращения польских элит к посредничеству России во внутренних спорах, тем самым постепенной потери суверенитета. В приложениях публикуются тексты обоих тайных посланий, переданных императрице А. Потоцким.